Central Arctic paleoceanography for the last 50 kyr based on ostracode faunal assemblages - Poirier, Robert K.; Cronin, Thomas M.; Briggs Jr, William M.; Lockwood, Rowan (Marine Micropaleontology, 2012)
The paleoceanography of the central Arctic Ocean was reconstructed for the last 50 kyr (Marine Isotope Stages (MIS) 1–3) based on ostracode assemblages from 21 14C-dated sediment cores from the Mendeleev, Lomonosov, and Gakkel Ridges. Arctic sediments deposited during the Holocene interglacial period (MIS 1), the Bølling–Allerød, and larger interstadial Dansgaard–Oeschger (DO) events (3–4, 8, and 12) contain abundant Cytheropteron spp., Henryhowella asperrima, and Krithe spp. at intermediate/deep-depths (~ 1000 to 3000 m). These assemblages suggest a ventilated deep, Arctic Ocean water mass similar to the modern Arctic Ocean Deep Water (AODW) during these time periods. In contrast, sediment deposited during stadial events corresponding to Heinrich events 1, 2, 3, and 4, (also possibly the Younger Dryas; YD), contain abundant Polycope spp. (60–80%) suggesting a greater influence of the Atlantic Layer (AL) on the Arctic Intermediate Water (AIW) and AODW. Reduced sea-ice during the early Holocene, the last deglacial, and MIS 3 interstadials is indicated by the reoccurrence of Acetabulastoma arcticum, an epipelagic species that is parasitic on sea-ice dwelling amphipods. One hypothesis to explain these oceanographic changes during longer stadial events, particularly within the last glacial period (MIS 2), involves sluggish ocean circulation, thicker sea-ice cover, and a deeper halocline with ocean exchange between Greenland Sea and Arctic Ocean deep-water through the Fram Strait.
id: 2283